2021
DOI: 10.3390/vaccines9121453
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking Native Display of CD0873 on Liposomes Augments Its Potency as an Oral Vaccine against Clostridioides difficile

Abstract: Mucosal vaccination aims to prevent infection mainly by inducing secretory IgA (sIgA) antibody, which neutralises pathogens and enterotoxins by blocking their attachment to epithelial cells. We previously demonstrated that encapsulated protein antigen CD0873 given orally to hamsters induces neutralising antibodies locally as well as systemically, affording partial protection against Clostridioides difficile infection. The aim of this study was to determine whether displaying CD0873 on liposomes, mimicking nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…To further test for the presence of antigen-specific IgG in vaccinated sera, 96-well plates were coated in recombinant protein antigen, either CD0873 or TcdB-RBD as previously described [ 25 , 47 ]. After blocking, sera diluted 1:10 were added and bound antibody detected using goat anti-hamster IgG Biotin-labelled secondary antibody and Streptavidin-HRP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further test for the presence of antigen-specific IgG in vaccinated sera, 96-well plates were coated in recombinant protein antigen, either CD0873 or TcdB-RBD as previously described [ 25 , 47 ]. After blocking, sera diluted 1:10 were added and bound antibody detected using goat anti-hamster IgG Biotin-labelled secondary antibody and Streptavidin-HRP.…”
Section: Resultsmentioning
confidence: 99%
“…NTCD T7 was chosen, as this strain was previously characterised for its biotherapeutic properties against CDI in the hamster model [ 45 , 46 ]. The colonisation factor, CD0873, was chosen as we showed that it induces colonisation blocking antibodies in hamsters when given as recombinant protein orally [ 25 , 47 ]. The receptor binding domain (RBD) of TcdB was chosen, as it is known to be immunogenic and to confer full protection in mice [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that outer membrane vesicles (OMVs) from E. coli encapsulated into Zein Nanoparticles coated with a Gantrez ® AN–Mannosamine Polymer Conjugate elicited high levels of IgG antibodies, while oral administration of the outer membrane protein alone did not elicit an antibody response ( 43 ). In contrast, displaying CD0873 on liposomes without encapsulation elicited significantly different IgG and IgA titers from the control group after three oral immunizations ( 44 ). Oral exposure to stx+ eae+ intimin-positive E. coli O157: H7 as an oral vaccine twice weekly for 6 weeks would increase resistance of cattle to colonization by wild-type E. coli O157: H7 following challenge ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…This strong immune response to CD0873 offered 80% protection from death in the study [ 121 ]. A subsequent study by Karyal et al demonstrated the use of liposomes to more effectively deliver the CD0873 antigen [ 122 ]. Not only does this appear to be the first use of a liposome delivery system for CDI vaccination, but this delivery strategy produced a more effective neutralizing antibody response as measured by greater inhibition of C. difficile adherence by vaccine-induced antibodies [ 122 ].…”
Section: Surface-antigen Mucosal Vaccinementioning
confidence: 99%
“…A subsequent study by Karyal et al demonstrated the use of liposomes to more effectively deliver the CD0873 antigen [ 122 ]. Not only does this appear to be the first use of a liposome delivery system for CDI vaccination, but this delivery strategy produced a more effective neutralizing antibody response as measured by greater inhibition of C. difficile adherence by vaccine-induced antibodies [ 122 ]. The authors indicated that the increased effectiveness of liposome-displayed CD0873 could be due to reduced protein aggregation, greater uptake of the vaccine by M cells, and interactions with macrophages due to the specific liposome composition.…”
Section: Surface-antigen Mucosal Vaccinementioning
confidence: 99%